Production cost of Orius insidiosus as biological control agent - Mendes, Simone Martins; Bueno, Vanda Helena Paes; Carvalho, Lívia Mendes; Reis, Ricardo Pereira (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to estimate the individual production cost of the predator Orius insidiosus (Say) in laboratory. A rearing model of O. insidiosus in laboratory was used to reach production of 33,000 individuals month-1, using 14.5% to maintain the predator rearing in the laboratory and 28,272 individuals for commercialization. The prices of different materials and equipments used on predator rearing were fixed at US 1.00 = R 2.84. The estimated cost for production of each adult predator was US 0.069, taking all the fixed and variable costs. This parameter is crucial to support O. insidiosus mass rearing, and to use this predator as biocontrol agent in biological control program of thrips.